Tissue-engineered repair material for pelvic floor dysfunction - Lin, Meina; Lu, Yongping; Chen, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Pelvic floor dysfunction (PFD) is a highly prevalent urogynecology disorder affecting many women worldwide, with symptoms including pelvic organ prolapse (POP), stress urinary incontinence (SUI), fecal incontinence, and overactive bladder syndrome (OAB). At present, the clinical treatments of PFD are still conservative and symptom-based, including non-surgical treatment and surgery. Surgical repair is an effective and durable treatment for PFD, synthetic and biological materials can be used to enforce or reinforce the diseased tissue. However, synthetic such as polypropylene patches caused a series of complications such as mesh erosion, exposure, pain, and inflammation. The poor mechanical properties and high degradation speed of the biomaterial meshes resulted in poor anatomical reduction effect and limitation of clinical application. Therefore, the current treatment options are suboptimal. Recently, Tissue engineered repair material (TERM) has been applied to repair PFD and could markedly improve the prognosis of POP and SUI repair surgery in animal models. Herein, we review the directions and progression of the TERM on POP and SUI repair. Adipose-derived stem cells (ADSCs) and endometrial mesenchymal stem cells (eMSC) appear to be suitable cell types for scaffold seeding and clinical implantation. The multidisciplinary therapy approach to tissue engineering is a promising direction for tissue repair. More and longer following-up studies are needed before determining the cell types and materials for PFD repair.